Pemidanaan Terhadap Pelaku Kekerasan Dalam Rumah Tangga (Putusan Nomor 129/Pid.Sus/2021/PN.SdaP): Punishment for Perpetrators of Domestic Violence (Decision Number 129/Pid.Sus/2021/PN.Sda) - Fadhil Pratama Putra; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2024)
Physical violence is defined as an act causing the victim pain, suffering, or significant losses. An example of domestic physical violence is found in Decision No. 129/Pid.Sus/2021/PN. Sda. This study investigates two key issues: 1) Whether the criminalization of perpetrators in Decision No. 129/Pid.Sus/2021/PN. Sda meets the provisions of Article 44 Paragraph (1) of Law Number 23 of 2004 concerning the Elimination of Domestic Violence? 2) Whether the punishment in Decision No. 129/Pid.Sus/2021/PN. Sda fulfills the objectives of criminal law? Using a normative juridical approach and library research method, the findings indicate that, per Article 44 Paragraph (1) of Law No. 23 of 2004, the perpetrator should have received a five-year prison sentence. However, the decision did not comply with this legal requirement. The study concludes that the punishment given does not align with the legislative model theory, suggesting a need for a five-year prison sentence. Moreover, the combined theory on the purpose of punishment, which includes providing a deterrent effect and offering guidance to the perpetrator, was not met in this decision. This highlights the necessity for a stricter application of the law to ensure both justice and rehabilitation.